2017
DOI: 10.3389/fneur.2017.00577
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of the Age-Dependent Efficacy of Multiple Sclerosis Treatments

Abstract: ObjectiveTo perform a meta-analysis of randomized, blinded, multiple sclerosis (MS) clinical trials, to test the hypothesis that efficacy of immunomodulatory disease-modifying therapies (DMTs) on MS disability progression is strongly dependent on age.MethodsWe performed a literature search with pre-defined criteria and extracted relevant features from 38 clinical trials that assessed efficacy of DMTs on disability progression. We fit a linear regression, weighted for trial sample size, and duration, to examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
181
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 224 publications
(200 citation statements)
references
References 39 publications
14
181
2
3
Order By: Relevance
“…MS‐DSS (Weideman et al., ) is assigned by a statistical model using gradient boosting machines. MS‐DSS includes disability measured by a highly sensitive CombiWISE (Kosa et al., ), mathematically adjusted for the efficacy of administered treatments using a published formula (Weideman, Tapia‐Maltos, Johnson, Greenwood, & Bielekova, ), the amount of CNS‐tissue destruction measured by the Combinatorial MRI Scale of CNS Tissue Destruction (COMRIS‐CTD) (Kosa et al., ), and additional features of lower variable importance, including demographic data. The model uses the following cross‐sectional data, listed in order of statistical importance: (1) therapy‐adjusted CombiWISE divided by patient age (CombiWISE/age); (2) CombiWISE; (3) COMRIS‐CTD; (4) time to first therapy, which measures the delay (in years) from disease onset to initiation of treatment; (5) difference in therapy‐adjusted and measured CombiWISE, which reflects the variant of the disease that is treatable by current immunomodulatory treatments; (6) age, and (7) family history of MS. MS‐DSS, the modeling outcome in the current study, is automatically calculated from user‐inputted raw data via a web interface (https://bielekovalab.shinyapps.io/msdss).…”
Section: Methodsmentioning
confidence: 99%
“…MS‐DSS (Weideman et al., ) is assigned by a statistical model using gradient boosting machines. MS‐DSS includes disability measured by a highly sensitive CombiWISE (Kosa et al., ), mathematically adjusted for the efficacy of administered treatments using a published formula (Weideman, Tapia‐Maltos, Johnson, Greenwood, & Bielekova, ), the amount of CNS‐tissue destruction measured by the Combinatorial MRI Scale of CNS Tissue Destruction (COMRIS‐CTD) (Kosa et al., ), and additional features of lower variable importance, including demographic data. The model uses the following cross‐sectional data, listed in order of statistical importance: (1) therapy‐adjusted CombiWISE divided by patient age (CombiWISE/age); (2) CombiWISE; (3) COMRIS‐CTD; (4) time to first therapy, which measures the delay (in years) from disease onset to initiation of treatment; (5) difference in therapy‐adjusted and measured CombiWISE, which reflects the variant of the disease that is treatable by current immunomodulatory treatments; (6) age, and (7) family history of MS. MS‐DSS, the modeling outcome in the current study, is automatically calculated from user‐inputted raw data via a web interface (https://bielekovalab.shinyapps.io/msdss).…”
Section: Methodsmentioning
confidence: 99%
“…11 Severe COVID-19 infections are more common in older adults (aged >60 years) with a higher case fatality rate. 6 Treatment decisions in this age group should be individualized, taking into account other comorbidities that increase the risk of death (cardiorespiratory disease and diabetes) 6 and the more modest benefits of diseasemodifying treatment in older patients 12 and/or those with progressive forms of MS. Pregnant women should follow general health advice during the COVID-19 pandemic, with no special considerations.…”
Section: Managing Special Patient Groupsmentioning
confidence: 99%
“…48 A meta-analysis of MS clinical trials found a larger reduction in relapses and MRI damage in a younger patient group, with a lack of difference between treated and untreated patients seen in patients older than age 40.5 years. 49 A population-based cohort in the United Kingdom found that patients (n = 104) treated initially with highly effective therapy had a lower mean change in EDSS at 5 years and a higher median time to sustained accumulation of disability than those treated with moderately effective therapies (n = 488). This effect persisted after adjustment for covariates including age and sex.…”
Section: The Reported Safety Profiles Of Some Highly Effective Agentsmentioning
confidence: 99%